The development of the Law of the Sea Convention the role of international courts and tribunals - 1979-; 1979- (Edward Elgar Publishing Limited, 2020)
The UN Convention on the Law of the Sea (UNCLOS) entered into force in November 1994. This insightful book offers in-depth appraisals of the contributions of jurisprudence to this major achievement of international law, tracing the impact that courts and tribunals have had on the development and clarification of various provisions of UNCLOS over the past quarter-century" -- Back cover.